Nutrition and food safety extension programming in urban Kansas City - Londa Nwadike (Urban Food Systems Symposium, 2020)
Kansas State University and the University of Missouri Extension Services conduct a great deal of programming in nutrition and food safety in urban areas of Kansas City (KC). This manuscript highlights the efforts of local and state-level Extension educators’ efforts across two different states and in four different counties. Information will be shared on low-income nutrition education, other nutrition education efforts, work with farmers’ market consumers and vendors, home food preservation, food preparation, and other related educational and outreach efforts. Methodologies used to work with underserved audiences and with community partners will also be outlined. All areas of Extension programming in urban areas face numerous challenges, which are also present in nutrition and food safety Extension programs. In urban areas, there are normally many other organizations providing similar services to those provided by Extension, including numerous non-governmental organizations (NGOs), hospitals, grocery stores, universities, and other entities. Therefore, it is essential for Extension personnel to partner with appropriate groups and focus on the comparative advantage that University Extension services can provide. Further, many people in urban areas are not familiar with Extension programming and need to be familiarized with what Extension is about and the value of working with or learning from Extension. In addition, populations in urban areas often tend to be more diverse and programming may likely need to be adapted to realities that community faces. Some examples of information that will be covered in the presentation include details about how the Wyandotte County Extension Nutrition Education program (in Kansas City, KS) has worked to personalize education for the diverse populations living in their county. This program has successfully trained community partners to assist with delivering evidence-based curricula to underserved audiences.
Keywords: outreach; health; metropolitan; university; education; partnerships